Human papillomavirus in head and neck cancer in India: Current status and consensus recommendations - Murthy, Vedang; Calcuttawala, Adnan; Chadha, Kirti; d’Cruz, Anil; Krishnamurthy, Arvind; Mallick, Indranil; Nair, Sudhir; Teni, Tanuja; Pawar, Sagar; Talapatra, Kaustav; Patil, Asawari; Bhatt, Amit; et al. (South Asian Journal of Cancer, 2017)
Abstract Human papillomavirus (HPV) associated head and neck squamous cell cancers (HNSCC) have become increasingly common in the West, but the same cannot be said about India. These cancers have a different biology and confer a better prognosis, however, its current role in the management of patients in India is not clearly defined. At the 35 th Indian Cooperative Oncology Network conference held in September 2016, a panel of radiation, surgical and medical oncologists, pathologists, and basic scientists from across the country having experience in clinical research with respect to HPV in HNSCC reviewed the available literature from India. All the ideas and facts were thereafter collated in this report. Various topics of controversy in dealing with the diagnosis and management of HPV-associated HNSCC have been highlighted in this report in context to the Indian scenario. Furthermore, the prevalence of the same and its association with tobacco and high-risk sexual behavior has been touched on. Conclusively, a set of recommendations has been proposed by the panel to guide the practicing oncologists of the country while dealing with HPV-associated HNSCC.